GPS-Based Digital Business Technology Innovation in Community Health Centers: Application Development for Health Staff Performance Management - Fitrani, Laqma; Angga Lisdiyanto (Information Technology International Journal, 2025)
Attendance management in community health centers (Puskesmas) often relies on manual procedures that are prone to inaccuracy, limited traceability, and weak verification mechanisms, particularly for staff performing field-based duties. These limitations hinder the effectiveness of performance monitoring and reduce administrative efficiency. This study aims to develop a GPS-based digital attendance system designed to enhance accuracy, accountability, and transparency in monitoring employee presence at Puskesmas Mantup. The research methodology comprises four stages: Observation to identify operational constraints; Planning and Analysis to formulate functional and non-functional requirements; System Design to model data structures, user interfaces, and workflow diagrams; and Implementation to develop the application using web technologies integrated with geolocation services. System functionality was validated through Blackbox Testing to ensure reliability across key processes, including login authentication, location validation, shift scheduling, and automated recording of attendance events. The results indicate that the system successfully performs real-time GPS verification, prevents false check-ins outside the designated radius, and supports both shift and non-shift attendance schemes. Additionally, the dashboard and reporting features provide comprehensive visibility for administrators in evaluating employee performance. Overall, the GPS-based attendance system substantially improves monitoring accuracy and operational efficiency, offering a scalable solution for adoption in primary healthcare settings.